Menggagas Fikih Media Sosial - Khariri, Khariri (Fakultas Syariah IAIN Purwokerto, 2019)
The development in the field of information technology in the era of industrial revolution 4.0 was so rapid. However, there are many negative findings from the use of social media, such as hoaxes, utterances of hatred, slander, etc. This requires a more contextual study of Islamic law (fiqh) and is able to answer what is the demand of the times, especially the phenomenon of social media. In carrying out the formulation of Islamic law, there are two methods of reasoning used, namely normative-deductive and empirical-inductive, so that the resulting laws can be in accordance with the demands of the community. Therefore, the idea of social media fiqh is to make an effort to find the maqÄá¹£id al-syarÄ«â€™ah (legal purpose) in the use of social media. By using the theory of sadd al-Å¼arÄ«â€™ah analysis, this study sought formulation of Islamic law in order to be a solution in the times. This theory is used to explore various problems that have occurred in the development of communication on social media. In addition, this study attempts to trace the exclusion (istinbÄá¹) of the law in formulating the fiqh of social media with the Uá¹£Å«l al-Fiqh approach and the social history of Islamic law. The work of this research is inseparable from the two legal provisions that have been formulated before, namely the MUI fatwa on Social Media and the Law of Information and Electronic Transaction.